PENERAPAN METODE SEQUENTIAL SEARCH UNTUK PENCARIAN DATA BUKU PADA PERPUSTAKAAN DAN KEARSIPAN PROVINSI BENGKULU - Ninosari, Devina; Mardiana, Yessi (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2023)
Bengkulu Provincial Library is a place, building or room to store books and other reading material organized and administered for reading, consultation and study in Bengkulu City. Increasing library materials in the library aka cause visitors have difficulty to find the desired book. To overcome this made the information system looking for books to facilitate the visitors find the desired book. This system is implemented using Sequential Search method, which is the process method for each element of the array one by one in a row, starting from the first element until the element is searched or all elements have been checked. Book search information system uses database system design and process design. The design process is. Which by the data flow diagram (DAD). Information System Search books generated can facilitate library visitors in searching the desired book.